Moral Value of Ijarah and Ujrah: Review of Rahn Concept in Islam - Lenny Yanthiani (UIN Sunan Gunung Djati Bandung, 2020)
Nowadays, Islamic pawning products have developed quite rapidly. In its operation, Islamic pawn products generally used the ijarah contract system. Ijarah agreement is a contract in the form of transferring the right to use goods and / or services through payment of rental wages, without being followed by the transfer of ownership of the goods themselves. In running a sharia pawn business, both Sharia Commercial Banks (BPRS), Sharia Rural Banks and also Islamic Pawnings were always guided by the fatwa of the National Sharia Board, which is a supervisory institution for Islamic and non-bank sharia financial institutions formed by the Indonesian Ulama Council (MUI).Therefore, this study aimed to describe and analyze the concept of ijarah and the aspects of ujrah in the realm of sharia pawnshop (rahn) especially in terms of how the benefits derived from a rahn product. The methodology used a qualitative approach (qualitative research), with a deductive style (deductive method). The results were in line with the fatwa of the National Sharia Council (DSN) no. 25 / DSN-MUI / III / 2002 which stated that the amount of storage service fees should not be determined based on the loan amount. The product organizers could only get benefit from the lease fees collected. This then constitutes the principles and values contained in the ijarah agreement and the ujrah aspects in the sharia pawnshop review (rahn).